Status of Polyembryony in Tree Borne Oilseeds-a Review - Chavan, S. B.; Keerthika, A.; Gunaga, R. P.; Uthappa, A. R.; Handa, A. K.; Jha, Ankur; Newaj, Ram; Dhyani, S. K.; Devi, S Vimala; Sridhar, K. B.; Shinde, P. P. (International Journal of Bio-resource and Stress Management, 2015)
Studies on mechanism in occurrence of polyembryony are vital for understanding the fundamental aspects of biology and also for practical purpose of genetic selection. Previously, polyembryony was reported in Mango and citrus; the commercial exploitation of it, in the field of Horticulture is well known. But, the reasons for occurrence is not clear, many authors have reported their observations and view about polyembryony. Similarly, the occurrence of polyembryony has been reported by plethora of workers in tree borne oil seeds at the nursery stage. The percentage occurrence of polyembryony in tree borne oil seeds ranges from 1 to 35% in Calophyllum inophyllum, Amoora rohituka, Madhuca latifolia, Ponammia pinnata, Azadirachta indica, Garcinia indica, Garcinia mangostana etc. But still, the topic is researchable and debatable due to lack of understanding in concept behind it. Generally, it is recommended to retain healthy shoots and cull out unhealthy ones for the growth and betterment of quality planting production. In this technology era, advance tools like markers can be used in identifying suitable reasons behind polyembryony and their potential in production of disease free seedling. Nowadays, the TBO’s are in prime focus to minimize the gap between demand and supply of fossil fuels and their sustainable use. Therefore, this article is framed in order to focus the lights on concept of polyembryony and their mechanisms and also the possibilities in exploring the potential of pathways of seed development in tree borne oil seeds-a researchable issue.